2017
DOI: 10.1159/000478629
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-122a Regulates Zonulin by Targeting EGFR in Intestinal Epithelial Dysfunction

Abstract: Background/Aims: This study aimed to investigate the role of microRNA (miR)-122a in regulating zonulin during the modulation of intestinal barrier. Methods: Zonulin proteins and their target gene expression were analyzed in miR-122a-overexpressing cell lines and in the target gene of epidermal growth factor receptor (EGFR). An mmu-miR-122a intestinal epithelial conditional transgenic (miR-122a-TG) mouse model was established to investigate EGFR and zonulin expression. MiR-122a was also detected in the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…MiR-122a also increases zonulin levels by decreasing the epidermal growth factor-receptor (EGFR) level and targeting the EGFR signaling pathways (A. Zhang, Wang, et al, 2017;B. Zhang, Tian, et al, 2017).…”
Section: Mirnas Tight Junctions and Intestinal Mucus Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-122a also increases zonulin levels by decreasing the epidermal growth factor-receptor (EGFR) level and targeting the EGFR signaling pathways (A. Zhang, Wang, et al, 2017;B. Zhang, Tian, et al, 2017).…”
Section: Mirnas Tight Junctions and Intestinal Mucus Barriermentioning
confidence: 99%
“…MiR-191a and miR-212 ZO-1 Weaken tight junctions Tang et al (2015) and L. Wang et al (2017) MiR-675 Cadherin E and ZO-1 Destructs tight junctions Zou et al (2016) MiR-874 Aquaporin 3 Weakens the intestinal barrier Su et al (2016), W. Zhang et al (2011), X. Zhi et al (2014 MiR-122a Zonulin Decreases EGFR level and targeting EGFR signaling pathways Increases the intestine permeability A. Zhang, Wang, et al (2017) andB. Zhang, Tian, et al (2017) MiR-21 PTEN/PI3K/Akt signaling Exerts destructive effect on intestinal barrier Regulates permeability of tight junctions C. Zhang, Xi, et al (2015), L. Zhang, Ke, et al (2015), and L. Zhang, Shen, et al (2015) MiR Note.…”
Section: Tight Junctions and Intestinal Mucus Barriermentioning
confidence: 99%
“…Hundreds of miRNAs have been described in humans, and an estimate of no less than 1000 miRNAs have been encoded by the human genome [4]. MiRNAs are involved in the regulation of gene expression in numerous critical biological processes [5], such as development, differentiation, apoptosis, and proliferation [6]. Upon structural analysis, the pre-translational level governance of miRNAs has been estimated to affect half of the human transcripts, whereas functional studies indicated that miRNAs might participate in almost every cellular process investigated to date [7].…”
Section: Introductionmentioning
confidence: 99%
“… Cichon et al (2014) reported that the intestinal barrier function is impaired in a typical Dicer1-deficient mouse model (i.e., absence of mmu-miR-192), resulting in spontaneous intestinal inflammation. Of note, miRNAs, such as miR-122a and miR-21, target negative regulators of immune response to promote inflammation ( Ye et al, 2011 ; Zhang et al, 2015 , 2017 ). Several investigations reveal that inflammatory cytokines such as tumor necrosis factor (TNF)-Ī± and interferon gamma (IFNĪ³) may increase greatly the expression of miRNAs in enterocytes, cultured cells, and intestinal tissues ( Ye et al, 2011 ; Haines et al, 2016 ).…”
Section: Fecal Mirnas As Potential Biomarkers For Intestinal Barrier mentioning
confidence: 99%